PERSEPSI TENTANG KEGIATAN MENGAJAR GURU PENGARUHNYA TERHADAP PEMBENTUKAN SIKAP HOMO ECONOMICUS YANG BERMORAL - Jun Suryanti, ; Laili Maslachah, (Pendidikan Ekonomi, 2010)
The objective of the present study was to examine the effect of the students perception about the teachers teaching activities on the development of the moral homo economicus attitude of the students at SMAN 2 Surabaya.  The population was the whole students of SMAN 2 Surabaya, while the sample was 70 students of the 12nd grade IPS-1 and IPS-2. The results of the study showed that the students perception about the teachers teaching activities  and the development of the moral homo economicus attitude of the students were good. It was also found that there was a significant influence of the students perception about the teachers teaching activities on the development of the moral homo economicus attitude.